Modeling spectral properties of X-ray sources for dosimetric Monte Carlo simulations of computed tomography: Influence on total energy deposition and spatial distribution of deposited energy - Steuwe, Andrea; Veloza, Stella; Skornitzke, Stephan; Pahn, Gregor; Kauczor, Hans-Ulrich; Stiller, Wolfram (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2018)
Purpose: X-ray spectra emitted by computed tomography (CT) sources differ in shape and mean spectral energy (Emean) due to different anode geometries, materials and filtration. Nonetheless, a variety of spectra and monoenergetic photons are employed in Monte Carlo (MC) simulations, despite possible differences in total energy deposition (Etotal) and its spatial distribution (Espatial). This study aims at assessing resulting differences and implications. Methods: The effect of different measured and generated 120 kVp-equivalent CT X-ray spectra on Etotal and Espatial in a water phantom (Ø = 32 cm, d=16 cm) was determined with MC simulations. Spectra were either measured in-house (reference: Emean,ref=57.7keV0° fan angle; and fan-angle dependent spectra (FADS)) or generated (online tool) without and with 3.3 mm aluminum filtration, the latter matching Emean,ref. Additionally, monoenergetic photons matching Emean,ref were applied. Simulations were performed with (FM) and without (NM) beam-shaping. Results: Compared to simulations employing the reference spectrum and using beam-shaping, relative differences in Etotal are: +2.2% (FADS), −5.4% (online tool, unfiltered), +0.1% (online tool, filtered) and −1.0% (57.7 keV). Maximum relative differences in Espatial are larger: −10% (FADS), −20% (online tool, unfiltered), −3% (online tool, filtered) and −20% (57.7 keV). Ignoring fan-angle dependent fluence modulation causes up to +50% difference in Espatial. Conclusion: For the use of different X-ray spectra, Etotal and Espatial are comparable for matching peak tube potential and Emean. Additionally, simulations of accurate Espatial require modeling of beam-shaping. Monoenergetic photons matching Emean,ref should not be employed for X-ray source emission modeling due to large inaccuracies in Espatial.